2021
DOI: 10.3390/molecules26113080
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Ciprofloxacin, Clarithromycin and Trimethoprim: Influence of pH and Humic Acids

Abstract: In view of the rising relevance of emerging pollutants in the environment, this work studies the photodegradation of three antibiotics, evaluating the effects of the pH of the medium and the concentration of dissolved organic matter. Simulated light (with a spectrum similar to that of natural sunlight) was applied to the antibiotics Ciprofloxacin (Cip), Clarithromycin (Cla) and Trimethoprim (Tri), at three different pH, and in the presence of different concentrations of humic acids. The sensitivity to light fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…This was achieved at optimum conditions of pH (6) and OLR (2 kgCODm −3 ·days −1 ), and an antibiotic concentration of 75%. The result obtained is in agreement with Conde-Cid et al [ 23 ], Rodríguez-López et al [ 12 ], and Haffiez et al [ 5 ] who reported pH as one of the most important parameters for maximizing the efficiency of pollutants from aqueous solutions. Thus pH affects the biodegradation process via the rate of the chemical reactions and generation of radicals in the process [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was achieved at optimum conditions of pH (6) and OLR (2 kgCODm −3 ·days −1 ), and an antibiotic concentration of 75%. The result obtained is in agreement with Conde-Cid et al [ 23 ], Rodríguez-López et al [ 12 ], and Haffiez et al [ 5 ] who reported pH as one of the most important parameters for maximizing the efficiency of pollutants from aqueous solutions. Thus pH affects the biodegradation process via the rate of the chemical reactions and generation of radicals in the process [ 5 ].…”
Section: Discussionsupporting
confidence: 91%
“…The biotic process involves biodegradation by microorganisms, while the abiotic processes are sorption, hydrolysis, oxidation-reduction, and photolysis [ 11 ]. Even though chemical, biological, and advanced oxidation processes have shown capabilities in eliminating organic contaminants and other derivatives, there is still limited knowledge on effective removal of ABs and other emerging contaminants using anaerobic digestion (AD) process, since some of them are bio-recalcitrant [ 1 , 4 , 12 ]. Therefore, this study investigated the biodegradation dynamics of two veterinary antibiotics viz.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of the antibiotics was performed following the methodology previously detailed in Rodríguez-López et al [ 24 ]. Briefly, the analysis was carried out in Ultimate 3000 HPLC equipment (Thermo Fisher Scientific, Madrid, Spain), with a quaternary pump, an auto-sampler, a thermostatted column compartment and an Ultimate 3000 series UV detector.…”
Section: Methodsmentioning
confidence: 99%
“…This increase in the toxicity exerted by AZI and CLA with the dose of the bio-adsorbent added separately and in mixtures may be due to the reduction in the degree of degradation affecting to these antibiotics as a result of increasing the pH of the solution (Sayadi et al, 2019;Rodríguez-López et al, 2021), which would be caused by the bio-adsorbents. Sayadi et al (2019) studied the effects of changing pH values on the degradation rate of azithromycin in the presence of nanoparticles, and concluded that the degradation of AZI was greater by decreasing the pH (maximum degradation of AZI at pH = 3).…”
Section: Macrolides: Azithromycin and Clarithromycinmentioning
confidence: 99%